Robust dynamic input reconstruction for delay systems - Kappel, Franz; Niaksimov, Vyacheslav (Zielona Góra: Uniwersytet Zielonogórski)
A problem of reconstruction of a non-observable control input for a system with a time delay is analyzed within the framework of the dynamical input reconstruction approach (see Kryazhimskii and Osipov, 1987; Osipov and Kryazhimskii, 1995; Osipov et al., 1991).
Keywords: delay system; input reconstruction; observation; robust algorithm